Local Autonomy: State-Centered Government Wrapped in Citizen-Centered Governance in the Tourism Development - Wijayanto, Purbayakti Kusuma; Zauhar, Soesilo; Hakim, Luqman; Said, Abdullah (FIA UB, 2020)
This city is called Batu Tourism City. Nine great modern-made tourism objects exist in this city. Four million tourist visits occur in this city. All built only since 16 years of local autonomy that they get. But many people said,